1988
DOI: 10.1520/jfs11948j
|View full text |Cite
|
Sign up to set email alerts
|

Gas Chromatographic/Mass Spectrometric Analysis of Morphine and Codeine in Human Urine of Poppy Seed Eaters

Abstract: In this study, poppy seeds were examined for a natural constituent that might serve as a marker for the seeds' ingestion as opposed to opiate abuse. Thebaine was selected as possible marker, since it was found to be a component of all poppy seeds examined and was not a natural component of different heroin samples. During the course of this investigation, a new extraction and cleanup procedure was developed for the gas chromatographic/nitrogen phosphorus detection (GC/NPD) and gas chromatographic/mass spectrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(28 citation statements)
references
References 5 publications
2
26
0
Order By: Relevance
“…Both mass spectra were characterized as thebaine by database mass spectral libraries due to its small size, the TMS group (electrophile) has probably reacted with the hydrogen at position 5 of thebaine in the present work. It should be noted that the formation of TMS derivative of thebaine could not be realized earlier by some workers [12] who reported the absence of this marker compound in the urine samples of poppy seed users. These authors employed acetyl derivatization for determining morphine and codeine in urine using acetic anhydride, a reagent known to cause degradation of thebaine to acetyl thebaol and/or 3,6-dimethoxy-4,5-epoxy-phenanthrene [25].…”
Section: Resultsmentioning
confidence: 74%
See 3 more Smart Citations
“…Both mass spectra were characterized as thebaine by database mass spectral libraries due to its small size, the TMS group (electrophile) has probably reacted with the hydrogen at position 5 of thebaine in the present work. It should be noted that the formation of TMS derivative of thebaine could not be realized earlier by some workers [12] who reported the absence of this marker compound in the urine samples of poppy seed users. These authors employed acetyl derivatization for determining morphine and codeine in urine using acetic anhydride, a reagent known to cause degradation of thebaine to acetyl thebaol and/or 3,6-dimethoxy-4,5-epoxy-phenanthrene [25].…”
Section: Resultsmentioning
confidence: 74%
“…Cassella et al [13] and Wu and Dobberstein [29] also reported a heat effect on decomposition of the alkaloid. On the other hand, thebaine was found to be stable in simulated gastric medium [12]. Therefore, it can be stated with a fair amount of certainty that the marker compound thebaine will be detected in most urine samples when opium is ingested by the oral route.…”
Section: Urinalysis Of Thebaine For Opium-use Markingmentioning
confidence: 99%
See 2 more Smart Citations
“…(c) The effects of acute ingestion of poppy seed pastries on the urinary excretion of morphine and codeine has been extensively reported ( Fritschi and Prescott Jr,1985;Hayes et al,1987;Pettitt et 41-4 al.,1987;Struempler,1987;ElSohly et al, 1988;ElSohly and Jones,1989;ElSohly and ElSohly, 1990;Selavka, 1991;Carpenter, 1994;Huestis and Cone, 1995). This data provides information on the maximum excretion of these two alkaloids following a one time ingestion.…”
Section: Discussion Of the Problemmentioning
confidence: 99%